Planned educational strategies based on learning styles: Case study PFM pedagogical-didactic induction - Velásquez, Gema Mercedes Bravo; Zambrano, Sandra Jamileth Basurto; Meza, Orley Benedicto Reyes (International research journal of management, IT and social sciences, 2022)
The research focuses on the systematization of experience that had as its object the "Pedagogical-Didactic Induction (planning) for teachers of physics and mathematics based on learning styles (theoretical, pragmatic, reflective and active), from the Experimental Science Management project of the Sciences Area of The Mathematics and Physics Specialization Education of the Redesign of the ULEAM, was based on the identification of the didactic strategies based on the class plan according to the learning styles in the students of the Millennium Educational Unit "Eugenio Espejo" in the year 2019. Considered that through class planning based on learning styles with strategies for each teacher, they achieve the quality of education at the time of executing the planning. The objective is to analyze the effectiveness of lesson plans with the four learning styles in physics and mathematics teachers in the second phase of the project's pedagogical induction. As technique for gathering information an interview checklist were applied to the teachers and students who participated in the project and the educational unit. In conclusion, relevant we have the importance of associating the class plan with learning styles helps to contribute greatly to educationmay increase the ease with which interested parties can locate our article.